مهجرو تاورغاء : نازحو المدينة المهجورة - Al-Ansari | الأنصاري, Abdul Wahid | عبد الواحد; Al-Muhaimid | المحيميد, Muhammad bin Odeh | محمد بن عودة; Massoud, Mohamed Ali (Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي, 2023)
This report includes important information and facts about the residents of the city of Tawergha - more than 40 thousand - in the northwest of Libya, whose residents supported the Gaddafi regime during the Libyan revolution that toppled it, and were accused during that of committing crimes against the residents of Misurata. | يتضمن هذا التقرير معلومات و حقائق مهمة حول سكان مدينة تاورغاء - و عددهم أكثر من 40 ألفا- في الشمال الغربي الليبي, التي وقف سكانها مع نظام تاقذافي خلال الثورة الليبية التي أطاحت به, واتهموا في اثناء ذلك بارتكاب جرائم بحق سكان مصراتة.